Estrategias innovadoras y su incidencia en el desarrollo integral de Educación intercultural de los estudiantes de Sexto año de EGB de la Unidad Educativa San Francisco de Asís - Ludeña Camacho, José Eduardo (2024)
Intercultural education strategies in Ecuador are a challenge faced in all its latitudes due to its multicultural and multiethnic nature; we are privileged to have a cultural richness in a small but geographically varied territory, which leads to social differences in each region, each one with its own ideology or life perspective. In a rule of law, which guarantees equality regardless of the ethnic group to which one belongs, it also includes the right to an integral education with respect for their cultures and ancestral beliefs. The present work studies innovative educational strategies that can have an impact on a more complete or enriching education when connecting with our cultural roots that we have preserved since colonial days and whose doctrines are maintained as customs, languages, celebrations, education, etc. The research problem is based on the relevance of innovation strategies in intercultural education and how they positively influence social interaction in the classroom, considering that having different origins, the way in which each student can be reached is different. Intercultural education prepares students to live in an increasingly globalized society, promoting understanding and appreciation of diversity. It is a primary must to guarantee inclusive and quality education for all students; in primary school intercultural education is essential for students, not only in the academic area, but also in the teaching of values and principles from an early age, in order to promote the integral development for the citizens training who are conscious of cultural diversity. Key words: Education, Interculturality, Strategies, Integrity, Inclusion.